2015
DOI: 10.1007/s11998-015-9693-0
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of supercooled water drops on cold solid substrates: initiation and mechanism

Abstract: Drops of liquid are placed on substrates having temperatures below the melting point of the liquids (supercooling). All well-known stages of cooling and freezing (supercooling-recalescence-main solidification-ice cooling) of water drops on both hydrophilic and hydrophobic surfaces were observed using a k-type thermocouple and an IR camera. Duration of the main solidification and the ice cooling stages were found to be dependent on the drop size. However, no conclusive relationship can be made regarding the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…There have been quite some debates about the initiation site of nucleation. Some authors [48][49][50] suggested that the nucleation preferentially starts at the three-phase contact line, while others 51,52 claimed that it starts randomly at the whole solid-liquid interface. The controversy might be caused by different test environment or Such a nucleation rate is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There have been quite some debates about the initiation site of nucleation. Some authors [48][49][50] suggested that the nucleation preferentially starts at the three-phase contact line, while others 51,52 claimed that it starts randomly at the whole solid-liquid interface. The controversy might be caused by different test environment or Such a nucleation rate is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For freezing-induced pinning, the literature offers various hypotheses for the criterion for contact line arrest [5][6][7][11][12][13]. For example, the delay in the arrest was argued to be caused by the requirement for a critical nucleus to form near the contact line [11,12]. However, a detailed description of growth of the nucleus in the presence of flow is lacking.…”
Section: A Mechanism Of Solidification-induced Pinningmentioning
confidence: 99%
“…Arrest of the drop can be due to temperature-dependent viscosity (generally diverging when approaching the melting point), or more dramatically due to solidification near the liquid/solid interface. Such cases were investigated for droplet impact [5][6][7][8]10], as well as for spontaneous spreading after gentle deposition on solid substrates [11][12][13]. Inkjet printing and applications such as spray coating indeed involve droplet impact.…”
Section: Introductionmentioning
confidence: 99%
“…Their study was focused on the arrest and spreading criterion of the puddle at the contactline, and found a pinning criterion based on a threshold value for the contact angle between the liquid and the basal solid. Another study revisited the pinning criterion in terms of critical frozen volume near the triple line 17 . More recently, a kinetic criterion based on the advancing velocity of a spreading drop was quantitatively and successfully tested 9 .…”
Section: Introductionmentioning
confidence: 99%